Solubility Measurement and Thermodynamic Study of Clotrimazole in Aqueous Mixtures of N-Methyl-2-Pyrrolidone at Various Temperatures: Study of Clotrimazole Solubility - Rezaei , Homa; Zhao , Hongkun; Rahimpour, Elaheh; Jouyban , Abolghasem (Iranian Journal of Pharmaceutical Sciences, 2023)
Clotrimazole is a broad-spectrum antifungal drug within the imidazole group that can potentially disrupt fungal cell ergosterol synthesis. It is a lipophilic molecule with a slow dissolution rate in water and poor aqueous solubility. Many efforts have been made in the literature to enhance clotrimazole’s solubility. Herein, with the aim of solubility enhancement, the solubility profile of clotrimazole in the aqueous binary mixtures of N-methyl-2-pyrrolidone at temperatures ranging from 293.2 to 313.2 K was investigated. The experimental solubility values were enhanced by increasing cosolvent composition and temperature. Furthermore, four mathematical cosolvency models were applied to correlate the solid-liquid equilibrium data, and the model accuracy results were shown as the mean relative deviation. Additionally, density values of saturated clotrimazole solution in the studied binary system were determined and reported. Gibbs and van’t Hoff equations were also employed to compute dissolution thermodynamic parameters at Thm=303 K.